An uncommon case of sarcomatoid urothelial carcinoma in covered bladder exstrophy. Issue 1 (1st January 2016) - Pavone, Carlo; Vella, Marco; Fontana, Dario; Scalici Gesolfo, Cristina; Oieni, Sebastiano; Toia, Francesca; Cordova, Adriana
Abstract: We report a case of a woman affected by covered exstrophy, uterus didelphys and external genital malformation presenting with advanced bladder cancer. After neoadjuvant therapy and anterior pelvic exenteration, the abdominal wall was reconstructed with a pedicled myocutaneous muscle-sparing vastus lateralis flap.